Application of Religious Harmony Values to Students of State Integrated Junior High School of Balaesang Tanjung - rahmawati, rahmawati; Saguni, Fatimah; Erniati, Erniati; Gusnarib, Gusnarib (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC EDUCATION, 2024)
The aim of study is to discussed the application of religious harmony values to students of State Integrated Junior High School of Balaesang Tanjung. This research adopts a qualitative approach. Qualitative research is characterized by collecting descriptive data, including the informants' words, actions, and feelings, who serve as the needed data sources. This study found that In implementing the values ​​of religious moderation at State Integrated Junior High School Balaesang Tanjung, namely through the principal’s policy followed by all teachers, especially Islamic religious education teachers at State Integrated Junior High School Balaesang Tanjung implementing the principles of religious moderation in every lesson, which includes the attitude of taking the middle path (tawassuth), straight and firm (i’tidāl), balance (tawāzun), tolerance (tasāmuh), egalitarian (musāwah), deliberation (syurā). The impact of implementing the values ​​of religious moderation at State Integrated Junior High School Balaesang Tanjung is that it has a positive effect on students, including growing an attitude of mutual understanding towards each other regardless of religion, being able to show an attitude of awareness and honesty, and not worrying about differences